Krafttraining vermindert die Erschöpfbarkeit von Patientinnen mit Fibromyalgie - Ammer, K. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2016)
Referat zur Arbeit von Ericsson A, Palstam A, Larsson A, Löfgren M, Bileviciute-Ljungar I, Bjersing J, Gerdle B, Kosek E, Mannerkorpi K. Resistance exercise improves physical fatigue in women with fibromyalgia: a randomized controlled trial. Arthritis Research & Therapy 2016; 18: 176